A study of photoelectric properties of grown SnSe2 crystal by direct vapour transport technique. (2022) - Patel, P.D.; Patel, H.M.; Sikligar, S.P.; Patel, P.B.; Desai, H.N.; Dhimmar, J.M.; Modi, B.P.
Abstract: The opto-electrical properties of Tin Diselenide (SnSe2 ) crystal are significant for application in photo detectors, optoelectronic devices and many more. Metal chalcogenide SnSe2 has been grown by direct vapor transport (DVT) technique. The chemical composition of grown crystal was studied by energy dispersive analysis of X-ray (EDAX). The photo detection property of SnSe2 crystal based photo detector was exploited for their envisioned applications in optoelectronics. SnSe2 crystals have observed an outstanding photo response ability at room temperature (300 K) with changing illumination intensities 50, 75, 100 and 125 mw/cm 2 . Moreover, the related parameters, photoresponsivity (R) spectral detectivity (D), external quantum efficiency (EQE), internal quantum efficiency (IQE) and trap depth parameters have been evaluated for pure SnSe2 crystal.